2020
DOI: 10.1016/j.ekir.2020.02.1024
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches to Arteriovenous Access Creation, Maturation, Suitability, and Durability for Dialysis

Abstract: Since the arteriovenous fistula (AVF) was first conceived over 50 years ago, the goal to create a vascular conduit with predictable and reproducible maturation and durability continues to elude caregivers. Recently, however, advances in the understanding of vascular biology and new technologies now provides us with some optimism; we are moving toward a viable solution. A quickly maturing, sustainable, and durable arteriovenous access may soon be attainable. This review will discuss these advances. There are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…The desired outcome for successful AVF maturation is a timely and properly arterialized vein via outward remodeling ( Hu et al, 2016 ), but AVF maturation failure ranges from 20 to 60% in observational studies ( Cheung et al, 2017 ). Improving AVF maturation remains an important clinical target for the management of ESKD patients ( DeVita et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The desired outcome for successful AVF maturation is a timely and properly arterialized vein via outward remodeling ( Hu et al, 2016 ), but AVF maturation failure ranges from 20 to 60% in observational studies ( Cheung et al, 2017 ). Improving AVF maturation remains an important clinical target for the management of ESKD patients ( DeVita et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…External shunt and internal arteriovenous fistula (AVF) are the two most common vascular access methods. [ 1 ] Creating an AVF to provide vascular access in hemodialysis patients has been shown to reduce morbidity and improve survival compared to catheters. [ 2 ] However, initial AVF maturation is unsatisfactory in up to 60% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…A number of novel therapies to promote maturation and maintain patency of arteriovenous accesses have shown promise. 9 Two techniques of percutaneous endovascular AVF (pAVF) creation have shown high success rates (87%-88%) in select patients. 10,11 A retrospective comparison of pAVFs to surgically created AVFs showed superior maturation for pAVFs but similar patency and percutaneous procedural rates.…”
mentioning
confidence: 99%
“…These devices have been tested in a small number of patients and the results are inconclusive at this time. 9 Recurrent stenosis, the most common cause for dysfunction in mature AVFs, requires repeated angioplasty. A recent randomized controlled trial, in patients with mature dysfunctional AVFs, showed decreased recurrence of stenosis at 6 months with paclitaxel-coated drug-eluting balloons compared to standard balloon angioplasty, thereby decreasing procedural burden.…”
mentioning
confidence: 99%
See 1 more Smart Citation